2022
DOI: 10.1039/d2ta05607k
|View full text |Cite
|
Sign up to set email alerts
|

Formulating electronic descriptors to rationally design graphene-supported single-atom catalysts for oxygen electrocatalysis

Abstract: Graphene-supported single-atom catalysts (G-SACs) have attracted considerable attention as promising candidates for oxygen electrocatalysis because of their low use of precious metals. However, the low specific activity resulting from insufficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…The practical value of a catalyst is an ensemble of performance and cost-effectiveness. Single-atom (SA) catalysts with atomically distributed reactive species have suggested a new strategy for maximizing the specific mass activity (MA) of precious metal catalysts. The optimal MA of precious metal catalysts can be achieved if each metal atom becomes an active site. However, SA catalysts always accompany inherent stability issues because thermodynamics propels the agglomeration of SAs into larger clusters or NPs. Therefore, SA catalysts with ultralow concentrations of precious metals are usually used to study the inherent catalytic nature of SAs, even though the low concentration worsens the overall conversion performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practical value of a catalyst is an ensemble of performance and cost-effectiveness. Single-atom (SA) catalysts with atomically distributed reactive species have suggested a new strategy for maximizing the specific mass activity (MA) of precious metal catalysts. The optimal MA of precious metal catalysts can be achieved if each metal atom becomes an active site. However, SA catalysts always accompany inherent stability issues because thermodynamics propels the agglomeration of SAs into larger clusters or NPs. Therefore, SA catalysts with ultralow concentrations of precious metals are usually used to study the inherent catalytic nature of SAs, even though the low concentration worsens the overall conversion performance.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve the stability issue and increase the loading of SAs, several atomic precision tuning of the chemical potential of SAs, for example, strengthening the SA-support interactions or driving the decomposition of NPs into SAs, is suggested. ,,, Several studies have reported that the electronic metal–support interaction (EMSI) improves catalytic activity and stabilizes and prevents agglomeration of metallic species. , For example, the Senftle group revealed that the reducibility of the support material and the oxophilicity of SAs concurrently affect the stability of SAs . Wei and coworkers confirmed that the increased EMSI between Au NPs and TiO 2 improves the catalytic performance of Au/TiO 2 for LT-WGSR .…”
Section: Introductionmentioning
confidence: 99%